SISTEM PENDUKUNG KEPUTUSAN PENERIMA BERAS MISKIN (RASKIN) DENGAN METODE WEIGHTED PRODUCT BERBASIS WEB PADA KELURAHAN PLELEN - Novi Rinawati (LPPM Universitas Sains dan Teknologi Komputer, 2024)
The Plelen Subdistrict Office is one of the government offices in Batang district, Central Java, which implements the RASKIN program, where the selection of prospective RASKIN recipients is still recorded manually. So that residents who should receive assistance will receive it according to the required criteria and will no longer be the wrong target for RASKIN recipients. Therefore, there is a need for a Decision Support System that can make it easier for sub-district employees to make decisions for residents who receive Poor Rice (RASKIN). With the existence of a decision support system (DSS), the aim is to make decisions more quickly and accurately. One method used is Weighted Product. The Weighted Product method is a method of determining order (priority) in multicriteria analysis and uses a multiplication technique to connect attribute ratings, where the rating of each attribute must first be raised to the power of the weight of the attribute in question.